Perianal mucinous adenocarcinoma diagnosed by histological study of anorectal abscess with fistula - Shir, Li Jee; Amin-Tai, Hizami; Nik Hisyamuddin Fathi, Nik Qisti Fathi; Jabar, Mohd Faisal (American College of Gastroenterology, 2018)
Perianal mucinous adenocarcinoma (PMA) is an oncologic rarity that poses a diagnostic and therapeutic dilemma for treating clinicians because there are few reported cases and an absence of definitive guidelines. We report a patient who had been treated with local surgery for recurrent perianal abscess with fistula for 3 years. Biopsy of the indurated tissue overlying his surgical scars revealed PMA. Neoadjuvant concurrent chemoradiotherapy followed by abdominoperineal resection was planned to address the locally advanced disease and ongoing sepsis. Our case is unique in that the fistula preceded carcinoma by only 3 years instead of the typical 10 years.